A comparative study of the seismic base shear force and story drift ratios using Time History and Modal Spectrum Analysis according to Peru Code E.030 and ASCE 7.16 on high-rise buildings - Quezada Ramos, Eder Nel (2020)
El texto completo de este trabajo no está disponible en el Repositorio Académico UPC por restricciones de la casa editorial donde ha sido publicado.